2008
DOI: 10.1016/s2005-2901(09)60006-6
|View full text |Cite
|
Sign up to set email alerts
|

A Neurovascular Transmission Model for Acupuncture-induced Nitric Oxide

Abstract: Acupuncture is the practice of inserting needles into the body to reduce pain or induce anesthesia. More broadly, acupuncture is a family of procedures involving the stimulation of anatomical locations on or in the skin by a variety of techniques. Employing acupuncture to treat human disease or maintain bodily condition has been practiced for thousands of years. However, the mechanism(s) of action of acupuncture at the various meridians are poorly understood. Most studies have indicated that acupuncture is abl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 83 publications
0
14
0
Order By: Relevance
“…It has also been suggested that cyclic Guanosine Monophosphate (cGMP) mediates the signaling functions of nitric oxide (NO) to improve local microcirculation [21]. A neurovascular transmission model for the acupuncture-induced NO effect has been proposed by Hsiao and Tsai [22]. In this model, the acupuncture stimulus is able to influence connective tissue via mechanical force transfer to the extracellular matrix (ECM).…”
Section: Discussionmentioning
confidence: 99%
“…It has also been suggested that cyclic Guanosine Monophosphate (cGMP) mediates the signaling functions of nitric oxide (NO) to improve local microcirculation [21]. A neurovascular transmission model for the acupuncture-induced NO effect has been proposed by Hsiao and Tsai [22]. In this model, the acupuncture stimulus is able to influence connective tissue via mechanical force transfer to the extracellular matrix (ECM).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that NO can upregulate Ang-1 expression after stroke, and the effects of inflammatory cytokines on the expression of Ang-1 and Ang-2 depend on their concentration: high concentrations of cytokines result in negative expression of Ang-1 and Ang-2, while low concentrations of cytokines result in positive expression of Ang-1 and Ang-2 [30-33]. Furthermore, EA can upregulate the NO level [34] and have an anti-inflammatory effect after stroke [35]. Accordingly, it is tempting to suppose that EA at the Zusanli (ST36) acupoint regulates the expression of Ang-1 and Ang-2 by increasing the NO level and decreasing inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…In a rabbit model of hepatic ischemia-reperfusion injury, EA at Yanglingquan (GB34) inbibited the production of iNOS in the liver, reduced the content of nitric oxide (NO) and malondialdehyde (MDA) and increased the activity of superoxide dismutase (SOD) (30). Likewise, in a rat model of streptozocin-induced Alzheimer's disease, a PD rat model, a hypothalamus of spontaneously hypertensive rats model, a cerebral ischemia-reperfusion injury rat model and a rabbit model of knee osteoarthritis, EA played pivotal roles on reducing oxidative stress by raising the content of SOD, lowering MDA or NO and even changing the blood distribution and microcirculation of various organs (31)(32)(33)(34)(35). Notably, EA affected the levels of SOD and MDA in different organs in a hyperlipemia rat model (36).…”
Section: Discussionmentioning
confidence: 99%